Does videourodynamic classification depend on patient positioning in patients with stress urinary incontinence?. Issue 7 (22nd August 2018) - Ecclestone, Hazel; Cashman, Sophia; Solomon, Eskinder; Pakzad, Mahreen; Hamid, Rizwan; Greenwell, Tamsin; Ockrim, Jeremy
Abstract : Introduction and Aims: Videocystometrogram (VCMG) is used to assess patients with SUI. A common classification system of SUI is the Blaivas and Olsson classification. The position this grading is performed in has never been established. Materials and Methods: One hundred twenty‐one women complaining of SUI refractory to conservative measures had video‐urodynamic assessment prior to operative intervention. Grading of stored video SUI image traces was assessed as per Blaivas and Olsson criteria by two independent investigators whilst women were both lying and standing with bladder at maximum cystometric capacity. Results: Seventy‐two (56.7%) patients' grading remained the same in both lying and standing positions. 49(40.5%) patients' grading altered on standing. twenty had non‐demonstrable incontinence converted to demonstrable incontinence and 29 had demonstrable incontinence on lying that changed grading on standing; 22 of these by one grade and seven by two grades (from I to IIb). A Fisher's exact test demonstrated a statistically significant difference in the distribution of SUI grading between supine and standing positions ( P  < 0.01). Conclusion: 40.5% of women have a changed Blaivas and Olsson grade of SUI when assessed standing as opposed to lying. This has implications for surgical treatment options and patient counselling. While the Blaivas and Olsson grading system for SUI is simple and reproducible there is little standardisation as to which position this grading is to be performed. We recommend that an international consensus is agreed upon in order for results to be comparable and to help with future outcome studies.